Don Diego Enríquez de Villegas in the lot of Mars. Struming the sword in the 17th century - Díaz Moreno, Félix (Anales de Historia del Arte, 2005)
Portuguese of birth Don Diego Enríquez de Villegas, served to the spanish crown along almost all his life. Sir and knight commander of the Order of Christ and captain of spanish cuirasses, developed an intense military activity. After a battle he remained disabled for the war devoting himself then to the study and elaboration of different agreements, standing out those ones dedicated to military topics and of education of princes. Their relations with important prominent figures of the Madrid court and specifically with other writers were productives and continuous.